(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This research aims to explore and compare the structural and semantic characteristics of phraseology in English and Uzbek languages, specifically within the context of political media discourse. The study delves into the distinctive linguistic features, idiomatic expressions, and their usage in political communication in both languages. By employing a comparative analysis, this research seeks to identify similarities and differences in the phraseological units used in political discourse in English and Uzbek, shedding light on the cultural and linguistic nuances inherent in these expressions.